Efforts to Increase Students' Interest in Learning Mathematics Based on the Wordwall Website - Sirait, Paisal; Wulandari, Putri; Rahmadani, Elfira; Masithoh, Ety (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Wordwall is an application that can be used as a learning media, learning resource and/or as an online assessment tool that is interesting for students. 37 Wordwall application is a website application that can be used to create learning media such as quizzes, matching, pairing, random words, word searches, grouping and so on. This research is motivated because students have low interest in learning mathematics. Interest is an activity carried out by students consistently in the learning process. Researchers conducted Class Action Research (CAR) as an effort to create active, creative and innovative learning that can increase students' interest in learning mathematics through the use of wordwall media in learning. CAR is carried out in two cycles. CAR is carried out in three cycles. Each cycle consists of planning, action, observation, and reflection activities. The results of the study showed that the analysis of students' interest in learning mathematics based on the wordwall website can increase students' interest in learning. In the results of cycle I, an increase in the good category was obtained with a percentage of 70% with 22 students in class VII-3 of SMPN 3 Kisaran, while in cycle II, students experienced an increase in learning interest with a very good category totaling 26 students in class VII-3 of SMPN 3 Kisaran with a percentage of 80%.